The formation of the Tatar-Muslim community in the Ik-Belaya interfluve in the 13th–14th centuries - Izmailov I.L (Золотоордынское обозрение, 2024)
To identify and define a complex of historical, archaeological and linguistic materials representing information about the population of the Ik-Belaya interfluve in the 13th–14th centuries. Research materials: The article uses materials of archaeological research, as well as written and epigraphic sources from the territory of the Ik-Belaya interfluve of the 13th–14th centuries. Novelty and results of the study: During the period of the Golden Horde (Ulus of Jochi), the agricultural and Muslim population from the Bulgarian ulus began to actively penetrate into the territory of the Ik-Belaya interfluve (Agidel-yurt) while the steppe zone was inhabited by a nomadic population. Earlier, only the Tatar military aristocracy penetrated into the Bulgarian ulus, but nomadic tribes did not do so. Later, the border between the settled agricultural and nomadic populations became dynamic due to the crisis in the Late Golden Horde period. The northern part of the Eastern Kama region remained exclusively developed by the Muslim agricultural population which later became the basis for the formation of the Tatar people.